Yoga and Music complement each other - Divya Acharya (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
Music and Yoga complement each other. Yoga is incomplete without music and music is incomplete without yoga. When we do yoga, music creates meditation in it and when we learn or sing music, yoga gives strength to it, so it seems very difficult to separate these two. But in today’s run-of-the-mill life, we cannot balance both, so we have to face incompleteness even without wanting to. Today many students start learning music but are unable to complete it. Because, sometimes lack of posture, sometimes lack of concentration, sometimes lack of attention, or any other reason, nowadays the era of shortcuts has come. Although yoga is a big subject, from the point of music, an attempt has been made to know, learn, and understand, which part of yoga practice is essential. In this article, 1. How can we understand the importance of time and complete the practice of music by doing some effective yoga practice while learning music? Similarly, 2. When we use music while doing yoga, a wonderful result is seen.